Design of Nonfullerene Acceptors with Near‐Infrared Light Absorption Capabilities. Issue 26 (18th July 2018) - Lee, Jaewon; Ko, Seo‐Jin; Seifrid, Martin; Lee, Hansol; McDowell, Caitlin; Luginbuhl, Benjamin R.; Karki, Akchheta; Cho, Kilwon; Nguyen, Thuc‐Quyen; Bazan, Guillermo C.
Abstract: A series of narrow bandgap electron acceptors is designed and synthesized for efficient near‐infrared (NIR) organic solar cells. Extending π‐conjugation of donor frameworks leads to an intense intramolecular charge transfer, resulting in broad absorption profiles with band edge reaching 950 nm. When blended with an electron donor polymer PTB7‐Th, IOTIC‐2F exhibits efficient charge transfer even with a small energetic offset, so as to achieve a large photogenerated current over 22 mA cm −2 with small energy losses (≈0.49 eV) in solar cell devices. With an intense NIR absorbance, PTB7‐Th:IOTIC‐2F‐based cells achieve a power conversion efficiency of 12.1% with good visible transparency (52% transmittance from 370 to 740 nm). Analysis of film morphology reveals that processing with solvent additives enhances crystalline features of acceptor components, while keeping an appropriate level of donor:acceptor intermixing in the binary blends. The incorporation of the third component, ITIC‐2F, into the PTB7‐Th:IOTIC‐2F blends increases the device efficiency up to 12.9%. The improvement is assigned to the cascaded energy‐level structure and desirable nanoscale phase separation of the ternary blends, which is beneficial to the photocurrent generation. This work provides an efficient molecular design strategy to optimize nonfullerene acceptor properties for efficient NIR organic photovoltaics. Abstract : A narrow bandgap nonfullerene acceptor, IOTIC‐2F, is designed and synthesized for near‐infrared organic solar cells (OSCs). By using solution‐processing fabrication, the IOTIC‐2F‐based single‐junction OSCs exhibit a power conversion efficiency up to 12.9% with a small open‐circuit voltage loss of ≈ 0.49 eV.